Analisis Faktor Optimisme terhadap Kesiapan Penerapan Rekam Medis Elektronik di Rumah Sakit Pertamina Bintang Amin - Sugiharto, Joko; Farich, Achmad; Angelina, Christin; Sudirahayu, Ika; Rachmawati, Rachmawati (Universitas Malahayati, 2024)
ABSTRACT The national e-health strategy aims to increase the accessibility and sustainability of quality health services through the use of information and communication technology, as well as supporting all components of the health system with effective, reliable and safe innovations. The integration of an electronic-based Health Information System (HIS) in all health service facilities is part of the Ministry of Health's 2020-2024 Strategic Plan, which focuses on strengthening fast, valid and resource sharing health information services. Readiness assessments are important to ensure successful implementation of the RME system by understanding the condition of health service facilities and the readiness of health workers to use the new system. Therefore, this research focuses on analyzing the optimism factor of health workers regarding the readiness to implement electronic medical records at Pertamina Bintang Amin Hospital in 2024. The research method used is quantitative with a cross-sectional design. The sample consisted of 157 respondents who were health workers tasked with implementing EMR using proportional random sampling techniques. The dependent variable assessed is readiness to implement RME, and the independent variables are optimism factor; social support, self-efficacy, self-esteem, and accumulated experience. The research results showed that the independent variables related to EMR implementation readiness are social support (p-value 0,024), self efficacy (p-value 0,047), and accumulated experience (p-value 0,003). The most dominant influencing factor is accumulated experience. Hospital management should carry out socialization about RME, expand infrastructure and provide training in developing the use of computers and electronic information systems to increase ICT literacy, mentoring and coaching programs to share direct experiences, rotation and assignment empowerment programs to develop new skills and insights, as well as providing given to employees who achievement/innovate to improve the readiness of health workers in implementing electronic medical record. Keywords: Electronic Medical Record, Implementation Readiness, Optimism, Hospital ABSTRAK Strategi e-kesehatan nasional bertujuan meningkatkan aksesibilitas dan kesinambungan layanan kesehatan berkualitas melalui pemanfaatan teknologi informasi dan komunikasi, serta mendukung seluruh komponen sistem kesehatan dengan inovasi yang efektif, handal, dan aman. Integrasi Sistem Informasi Kesehatan (SIK) berbasis elektronik di semua fasilitas pelayanan kesehatan merupakan bagian dari Rencana Strategis Kementerian Kesehatan 2020-2024, yang fokus pada pemantapan layanan informasi kesehatan yang cepat, valid, dan resource sharing. Penilaian kesiapan penting untuk memastikan keberhasilan penerapan sistem RME dengan memahami kondisi fasilitas layanan kesehatan dan kesiapan petugas kesehatan dalam menggunakan sistem baru. Oleh karena itu, penelitian ini fokus pada analisis faktor optimisme petugas kesehatan terhadap kesiapan penerapan rekam medis elektronik di RS Pertamina Bintang Amin pada tahun 2024. Metode penelitian yang digunakan adalah kuantitatif dengan desain cross-sectional. Sampel terdiri dari 157 responden yang merupakan tenaga kesehatan yang bertugas menerapkan RME dengan menggunakan teknik proporsional random sampling. Variabel dependen yang dinilai adalah kesiapan penerapan RME, dan variabel independen adalah faktor optimisme; dukungan sosial, kepercayaan diri, harga diri, dan akumulasi pengalaman.Hasil penelitian didapatkan variabel independen yang berhubungan dengan kesiapan penerapan RME adalah dukungan sosial (p-value 0,024), kepercayaan diri (p-value 0,047) dan akumulasi pengalaman (p-value 0,003). faktor paling dominan yang berpengaruh adalah akumulasi pengalaman. Manajemen rumah sakit hendaknya melakukan sosialisasi tentang RME, memperluas infrastruktur dan penyediaan pelatihan pengembangan penggunaan computer-sistem informasi elektronik untuk peningkatan literasi TIK, program mentoring dan coaching untuk saling berbagi pengalaman langsung, program rotasi dan pemberdayaan tugas untuk mengembangkan kemampuan dan wawasan baru, serta pemberian penghargaan kepada karyawan yang berprestasi/berinovasi untuk meningkatkan kesiapan petugas kesehatan dalam penerapan rekam medis elektronik. Kata Kunci: Kesiapan Penerapan Rekam Medis Elektronik, Optimisme, Rumah Sakit